Improved microwave absorption properties by atomic-scale substitutions. (November 2018) - Li, Yixing; Liu, Xiaofang; Liu, Rongge; Pang, Xueyong; Zhang, Yanhui; Qin, Gaowu; Zhang, Xuefeng
Abstract: To solve the electromagnetic impedance matching issue, microwave absorption materials are usually composed of magnetic and dielectric components with heterogeneous interfaces at micro/nanoscales. Herein we demonstrate an arc-discharging approach to optimize microwave absorption properties of magnetic@dielectric Fe@C nanocapsules by in-situ substituting nitrogen heteroatoms in graphitic layers. By increasing the nitrogen content, we find that the electromagnetic properties can be effectively tuned, presenting the decreased transmission, the increased absorbance and the slight change for the reflection efficiencies. Experimental and theoretical results reveal that nitrogen dopants result in the atomic-scale symmetry breaking, inducing the separation of space charge at nitrogen-substituted sites, which play a role of electric dipole for the electromagnetic polarization. The present study has important significance in understanding the structural origin of microwave absorption, and meanwhile provides an effective way for designing microwave absorbents at atomic-scale. Graphical abstract: Image 1